(untitled) (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2025)
In line with a multidimensional and dynamic understanding of giftedness, which assumes that the promotion of giftedness is talent development, teaching must be designed in such a way that all students are enabled to develop their potential and talents. In cooperation between science education and school practice, elements for potential- and talent-oriented biology education have been developed. In this article, the different elements are theoretically located and concrete examples are presented.